Online World Conference and Expo, October 12-14, 1998 Washington, D.C. - Flora G. Shrode (Issues in Science and Technology Librarianship)
Online, Inc. sponsors the annual Online World conference where librarians, Internet researchers, managers, and information professionals from all types of organizations gather to share their expertise and to learn about new products and services from vendors. Major themes at Online World '98 were web search engines, making electronic information sources available to users, and intranets.